The hydration of carbonyl compounds - Evans, P (1964)
A method has been evolved for the study of the kinetics of the dehydration of carbonyl compounds. The basis of this method is shown in the reaction scheme given below: OH \ / &nbspC; / \ slow → \ C / = O + H2O OH \ C / = O + scavenger fast → adduct The scavengers used were semicarbazide, hydroxylamine, phenylhydrazine and sulphite. Experiments with sulphite as scavenger were followed by titration on an automatic pH stat titrator. OH SO3- \ / &nbspC; / \ + SO3- → \ / &nbspC; / \ + OH− OH OH The progress of the reaction with other scavengers was followed by ultra-violet spectrophotometric techniques. Another reaction scheme suggested by earlier workers1 as a possible method of studying the kinetics of the dehydration of formaldehyde was investigated and shown both on theoretical and practical grounds to be of no value in providing kinetic data. This scheme was as shown below: OH / H2C \ slow ⇋ HCHO + H2O OH involatile volatile ↓ fast to gas stream The scavenger techniques were used to study the kinetics of the dehydration of formaldehyde and acetaldehyde. These reactions are subject to general acid-base catalysts. Formaldehyde was studied in detail, a large number of catalysts of varying structures, charge types etc. being investigated [2,3,4.] →. Acetaldehyde had already been extensively investigated by previous workers. The present work gave results in good agreement with the earlier work. This work was however of special interest in that recent work by Gruen and MoTigue5 had raised doubts as to the validity of the "thermal maximum" method which had been employed in obtaining the majority of the previous acetaldehyde results. The results obtained for a wide range of catalysts for formaldehyde conformed with one exception, azide, to two single Brönsted relationships to within log ± 0.5 over sixteen pK units. These relationships were: Acid catalysis: (12 catalysts studied) kA p = 0.46 [ qk p ] 0.23 Base catalysis: (29 catalysts) kB q = 2.0 x 10-4 [ p qk ] 0.40 where kA and kB are the catalytic constants in 1.mole-1 sec-1, p and q the statistical factors and k the conventional acid-base strength of the catalyst. The types of catalysts studied included carboxylic acids, nitrogen compounds and inorganic acids, e.g. HF, H2AsO4−, H6TeO6. In the light of these catalytic results the general range of validity of the Brösted relationships is discussed. The effects of statistical factors steric and charge effects are also reviewed. The formaldehyde results are compared with those from other carbonyl hydration studies. The somewhat anomalous carbon dioxide hydration results of Sharma and Danckwerta6 are discussed. The results are also of interest in that they verify some earlier polarographic results7,8 giving credence to the reliability of the mathematical approximations made in obtaining the polarographic data.